Analisis Determinan Rumah Tangga Miskin di Riau: Pengukuran Indeks Kemiskinan Multidimensi - Damaiyanti, Desi; Harlen, Harlen; Widayatsari, Any (Jurnal Dinamika Ekonomi Pembangunan, 2023)
Poverty is a multidimensional issue, necessitating a multidimensional approach to complement existing poverty alleviation efforts. Utilizing household microdata from the National Socioeconomic Survey (SUSENAS) 2018–2022 and the Alkire-Foster method, this study aims to measure poverty based on various levels of deprivation experienced by the population. The study examines three dimensions: education, health, and living standards. The findings reveal disparities between poverty measured solely through monetary aspects and poverty measured by considering multiple dimensions. The proportion of the population living in multidimensional poverty is greater than those living in monetary poverty, indicating that even if individuals are not economically poor, they remain deprived across various poverty dimensions. In Riau Province from 2018 to 2022, the health dimension had the highest contribution to multidimensional poverty, followed by living standards and education.